Mobile location in GSM networks using database correlation with bayesian estimation - Khalaf-Allah, Mohamed; Kyamakya, Kyandoghere (Proceedings - IEEE Symposium on Computers and Communications, 2006)
We present a database correlation method combined with Bayesian estimation for mobile location in GSM networks. The final location request can be estimated using different ways. Three methods are introduced and investigated in terms of location accuracy. Field measurements with off-line simulations have been performed in a suburban area, which is the dominant environment type in many parts of European cities. We think that location accuracy requirements in such environments should be relaxed, otherwise more work have to be conducted to achieve accuracies comparable to those in urban and dense urban areas. © 2006 IEEE.
Created from Fastlane, Scopus look-up